Handbook of competence and motivation - Covington, Martin V.; Dweck, Carol S., 1946-; Elliot, Andrew J. (Guilford Press, 2005)
In one volume, this important handbook provides a comprehensive, authoritative review of achievement motivation and establishes the concept of competence as an organizing framework for the field. The editors synthesize diverse perspectives on why and how individuals are motivated in school, sport, work, and other settings. Written by leading investigators, chapters reexamine central constructs in achievement motivation; explore the impact of developmental, contextual, and sociocultural factors; and analyze the role of self-regulatory processes. Focusing on the ways in which achievement is motivated by the desire to experience competence and avoid experiencing incompetence, the volume integrates disparate theories and findings and sets forth a coherent agenda for future research.